(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information on the history of the origins of English and Uzbek languages, as well as facts about which groups these two languages belong to. There is also information about adverbial clauses of time English and Uzbek languages, their differences. Syntax information is also provided. Information on the syntax structure of English and Uzbek is also provided. One thing is for sure, English and Uzbek are completely different. This is because the two languages belong to different language families. It is also known that each language has its own aspects. Although they differ in grammar and letters, languages serve humanity. There are so many languages in the world today. But 6 languages are recognized as world languages. Undoubtedly, English tops the list of world languages. This article provides information on the phonetics and syntax of the world-famous language, English and Uzbek. This information is of course supplemented with examples.